PELATIHAN DAN PENDAMPINGAN KADER POSPAUD DALAM PENGELOLAAN MODEL PEMBELAJARAN YANG AKTIF DAN KREATIF - Hasrul Hasrul; Wasliaty Sirajuddin; Aslinda Hafid (Universitas Muhammadiyah Tapanuli Selatan, 2022)
This community partnership program is “Training and Assisting POSPAUD Cadres in the Management of Active and Creative Learning Models”. This program aims to improve the knowledge and skills of cadres in managing active and creative learning models such as planning learning activities and learning materials that are appropriate to the developmental stages of children by utilizing educational game tools (APE). so that it will have an impact on the quality of learning in POSPAUD. This PKM was carried out at the POSPAUD